Building Community via Sport for Adolescents - Stacy Warner; Stephen Leierer (Journal of Applied Sports Management, 2015)
Sport is frequently claimed to foster a greater sense of community for participants. However, a dearth of quantifiable and empirical evidence supports this claim and even less is known about how sport impacts adolescents' sense of community. The aim of this research was to assess the effectiveness of a sport program for adolescents. A pre/post research design was used to determine if any changes in sense of community were experienced for adolescents who took part in a three-week sport program. Sense of community was measured using the Sense of Community Index- 2. A total of 28 participants completed pre- and postsurveys. These data were analyzed and the findings indicated that significant increases in adolescents' sense of community were observed. An analysis of the survey subscales revealed that the adolescent program participants in the study experienced significant increases related to Reinforcement of Needs, Membership, Influence, and Shared Emotional Connections. This study helps lay the foundation for better understanding of how sport can help build a sense of community for adolescents.
Keywords: Community building; sense of community; adolescents; participatory sport; community